2004
DOI: 10.1289/ehp.6897
|View full text |Cite
|
Sign up to set email alerts
|

Personal Exposure to Submicrometer Particles and Heart Rate Variability in Human Subjects

Abstract: We conducted a study on two panels of human subjects—9 young adults and 10 elderly patients with lung function impairments—to evaluate whether submicrometer particulate air pollution was associated with heart rate variability (HRV). We measured these subjects’ electrocardiography and personal exposure to number concentrations of submicrometer particles with a size range of 0.02–1 μm (NC0.02–1) continuously during daytime periods. We used linear mixed-effects models to estimate the relationship between NC0.02–1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 29 publications
5
85
1
2
Order By: Relevance
“…Therefore, the exposure levels reported in this investigation must be interpreted with caution as they are likely conservative estimates of actual exposures in transportation environments. Nevertheless, the majority of particles produced by gasoline and diesel vehicles are between 0.02 and 0.1 mm in diameter (Morawska and Zhang, 2002), and previous studies employing P-TRAKs have observed significant associations between UFP counts and oxidative DNA damage (Vinzents et al, 2005) as well as changes in heart rate variability (Chan et al, 2004) and vasoconstriction (Rundell et al, 2007). Therefore, while the P-TRAK is not the most sensitive instrument available, it remains a valuable instrument in environmental epidemiology owing to its portability and relatively low cost.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, the exposure levels reported in this investigation must be interpreted with caution as they are likely conservative estimates of actual exposures in transportation environments. Nevertheless, the majority of particles produced by gasoline and diesel vehicles are between 0.02 and 0.1 mm in diameter (Morawska and Zhang, 2002), and previous studies employing P-TRAKs have observed significant associations between UFP counts and oxidative DNA damage (Vinzents et al, 2005) as well as changes in heart rate variability (Chan et al, 2004) and vasoconstriction (Rundell et al, 2007). Therefore, while the P-TRAK is not the most sensitive instrument available, it remains a valuable instrument in environmental epidemiology owing to its portability and relatively low cost.…”
Section: Discussionmentioning
confidence: 94%
“…Specifically, increases in ambient UFP counts of approximately 10,000/ cm 3 have been associated with increases in daily mortality of 3% (Sto¨lzel et al, 2006) and 4.5% (Wichmann et al, 2000), respectively, with a lag of 4 days. Similar increases in personal UFP exposures have also been associated with decreased heart rate variability among subjects with impaired lung function (Chan et al, 2004). Indeed, the impact of UFP exposures may be most troubling for individuals suffering from asthma or obstructive pulmonary diseases as pulmonary deposition is greatest for these individuals (Brown et al, 2002;Chalupa et al, 2004;Frampton et al, 2004).…”
Section: Introductionmentioning
confidence: 92%
“…However, the Grimm OPC provides good temporal resolution of particle mass size distribution. In previous studies, PM measurement results obtained by a Grimm OPC approximated (± 15%) those of a reference sampler at urban sites (Chan et al, 2004;Giugliano et al, 2005;Grimm and Eatough, 2009;Cheng and Li, 2010;Hansen et al 2010;. In this study, the measured particle mass size distribution was determined using DistFit software (Chimera Tech., Inc., Forest Lake, MN, USA), and the PM 10 and PM 2.5 levels were calculated as fractions of particle mass size distribution (Cheng and Lin, 2010).…”
Section: Sampling Equipmentmentioning
confidence: 90%
“…Considerably more studies have addressed the problem of environmental exposure to particulate air pollution. Their findings indicate that elevated concentrations of particulate dust are associated with a decreased SDNN and SDANN [8,14,15,[51][52][53][54]. It is difficult to compare our results with the studies of other authors, because they were conducted among people environmentally exposed to dusts, where other harmful factors could be also present.…”
Section: Discussionmentioning
confidence: 64%
“…Inhaled ambient air particles in low concentrations stimulate receptors in the lungs, thereafter, the impulses are transmitted centrally by vagal nerves and processed in medulla and cerebral cortex. This causes apnea with bradycardia, vasodilatation and systemic hypotension [54]. Markedly, the increased parasympathetic activity may have adverse consequences in some circumstances, for example in the presence of long QT syndrome or poisonings with different substances, it may lead to bradyarrhythmia [50].…”
Section: Discussionmentioning
confidence: 99%